Depressive symptoms in community-dwelling persons aged ≥60 years in Inanda, Ntuzuma and KwaMashu in eThekwini, KwaZulu-Natal - Jayalakshmi Narainsamy; Jennifer Chipps; Bilkish Cassim (South African Journal of Psychiatry, 2015)
Background. Physical and psychological ailments increase with age; while the physical ailments are well documented, mental health issues have received less attention.